Philosophy of language - Soames, Scott (Princeton foundations of contemporary philosophy., 2010)
In this book one of the world's foremost philosophers of language presents his unifying vision of the field--its principal achievements, its most pressing current questions, and its most promising future directions. In addition to explaining the progress philosophers have made toward creating a theoretical framework for the study of language, Scott Soames investigates foundational concepts--such as truth, reference, and meaning--that are central to the philosophy of language and important to philosophy as a whole. The first part of the book describes how philosophers from Frege, Russell, Tarski, and Carnap to Kripke, Kaplan, and Montague developed precise techniques for understanding the languages of logic and mathematics, and how these techniques have been refined and extended to the study of natural human languages.